Switchable acoustic and optical resolution photoacoustic microscopy for in vivo small-animal blood vasculature imaging - Moothanchery, Mohesh (2017)
Photoacoustic microscopy (PAM) is a fast-growing invivo imaging modality that combines both optics and ultrasound, providing penetration beyond the optical mean free path (~1 mm in skin) with high resolution. By combining optical absorption contrast with the high spatial resolution of ultrasound in a single modality, this technique can penetrate deep tissues. Photoacoustic microscopy systems can have either a low acoustic resolution and probe deeply or a high optical resolution and probe shallowly. It is challenging to achieve high spatial resolution and large depth penetration with a single system. This work presents an AR-OR-PAM system capable of both high-resolution imaging at shallow depths and low-resolution deep-tissue imaging of the same sample in vivo. A lateral resolution of 4 µm with 1.4 mm imaging depth using optical focusing and a lateral resolution of 45 µm with 7.8 mm imaging depth using acoustic focusing were successfully demonstrated using the combined system. Here, in vivo small-animal blood vasculature imaging is performed to demonstrate its biological imaging capability.